SOSIALISASI BAHAYA KECACINGAN PADA ANAK-ANAK DI DESA LEUPEUNG ULEE ALUE - Desreza, Nanda; Dentalistya, Hilma; Afriana, Fira Nur; Khairunnisa, Mutia; Nadiya, Deski; Rohid, Teuku Muhammad; Bengi, Simah; Munte, Wahyu Rezeki; Marliza, Riska (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2022)
Helminthiasis is a disease caused by intestinal parasitic worms with a relatively high prevalence that spreads throughout Indonesia. While not fatal, this disease gradually affects the health and productivity of those infected through a decline in nutritional status. Its slow-progressing nature and tendency to be asymptomatic classify helminthiasis as a neglected disease. According to data from the World Health Organization (WHO), more than 1 billion people are infected with Ascaris lumbricoides, 795 million people with Trichiuris trichiura, or 740 million people with hookworm. The results obtained from socialization activities conducted in Leupeung Ulee Alue Village, Aceh Besar, indicate that the community still has limited understanding of the dangers posed by helminthiasis and the factors that can lead to infection. This community engagement initiative aims to provide the residents of Leupeung Ulee Alue Village with a better understanding of this disease.